The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14237450
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanical, Sound Absorption and Thermal Properties of Cellular Rubber Composites Filled with a Silica Nanofiller

Abstract: This paper deals with the study of cellular rubbers, which were filled with silica nanofiller in order to optimize the rubber properties for given purposes. The rubber composites were produced with different concentrations of silica nanofiller at the same blowing agent concentration. The mechanical, sound absorption and thermal properties of the investigated rubber composites were evaluated. It was found that the concentration of silica filler had a significant effect on the above-mentioned properties. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Low hardness of the composites can also be attributed to the high resilience of the same . 38 Generally, resilience decreases with the increase in hardness and hence the resilience results are in agreement with the hardness results (Figure 11). Moreover, It can be concluded that higher Cu-g-graphite loadings in NR composites lead to higher ability to transform mechanical energy into heat, and thus to a decrease in the rebound resilience.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Low hardness of the composites can also be attributed to the high resilience of the same . 38 Generally, resilience decreases with the increase in hardness and hence the resilience results are in agreement with the hardness results (Figure 11). Moreover, It can be concluded that higher Cu-g-graphite loadings in NR composites lead to higher ability to transform mechanical energy into heat, and thus to a decrease in the rebound resilience.…”
Section: Resultssupporting
confidence: 85%
“…Similar observations have been reported for silica nanofiller filled cellular rubber composites. 38
Figure 11.Resilience of Cu-g-graphite/NR composites.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1], the authors investigated the mechanical, acoustic, and thermal properties of cellular rubber composites, which were produced with different concentrations of silica nanofillers at the same blowing agent concentration. It was found that a higher concentration of silica nanofillers generally led to an increase in the mechanical stiffness and thermal conductivity and to a decrease in the sound absorption and thermal degradation of the investigated rubber composites.…”
mentioning
confidence: 99%